Dynastic politics and political party recommendation patterns in the 2017 Batu City regional head election - Didik Supriyanto (The International Journal of Politics and Sociology Research, 2023)
The strong grip of the oligarchy has resulted in the mechanism for providing recommendationsupport from political parties not running properly, there is a tendency to nominate candidates based on political elites instead through a democratic mechanism that considers the integrity and capabilities of the candidate. Study This research uses descriptive qualitative research. Data collection techniques using interviews, observation and documentation. The data obtained then goes through the stages of selecting data, clarifying data, and organize data. The findings of this study indicate that the pattern of recruitment for political parties (PDIP) is carried out openly, but through consideration of family existence. Besides that the presence of Edy Rumpoko provided a major advantage in influencing the support of political parties. The results of the study show that (1) the PDIP recruitment pattern for Dewanti Rumpoko is carried out in a systematic way open according to the regulations and regulations in force, but outside of that the existence of incumbent figures and popularity is always nominated, and is the main attraction of PDIP in carrying Dewanti Rumpoko in the Pilkada Batu City, (2) the promotion of Dewanti Rumpoko is still affiliated with the existence of Edy Rumpoko in behind it.